M-CASH: Simple Software for MSME Financial Report Management in an Effort to Support SDGs to Drive Economic Growth - Cahyani, Meti Regita; Zulpahmi; Rahayu, Dewi Pudji; Larasati, Meita (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to design a simple website-based financial reporting software for MSMEs to be more advanced in supporting inclusive and sustainable economic growth in accordance with the Sustainable Development Goals (SDGs). The subject of this research is MSME players at the Tugas Ibu Foundation. This research uses secondary data in the form of financial data contained in the balance sheet and profit and loss. The data analysis technique uses descriptive methods. The research method uses research and development (R&D) with a 4D development model modified into 3D by going through several stages, namely defining, design, and development. The results of this study are in the form of simple web-based M-CASH software that can help MSME actors record financial reports.